2015
DOI: 10.5114/wiitm.2015.54223
|View full text |Cite
|
Sign up to set email alerts
|

Micropercutaneous nephrolithotripsy: initial experience.

Abstract: IntroductionFor small renal calculi (< 2 cm) the currently available treatment options include extracorporeal shockwave lithotripsy (ESWL), retrograde intrarenal surgery (RIRS) and standard/mini percutaneous nephrolithotomy (PNL). A new method, microperc, has therefore been developed, in which a smaller tract size and smaller instruments were used.AimTo present our clinical experiences with micropercutaneous nephrolithotripsy (microperc) in the treatment of small renal calculi.Material and methodsWe retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Ölçücüoğlu et al. 14 found that the curative effect of an F4.8 visual puncture system in combination with holmium laser lithotrity was effective for the treatment of calculi <2 cm, and that the wound size was reduced and the success rate of channel establishment improved. Silay et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ölçücüoğlu et al. 14 found that the curative effect of an F4.8 visual puncture system in combination with holmium laser lithotrity was effective for the treatment of calculi <2 cm, and that the wound size was reduced and the success rate of channel establishment improved. Silay et al.…”
Section: Discussionmentioning
confidence: 99%
“…Non-enhancing CT was used to evaluate patients at 1-month and 3-month follow-up. Clinically insignificant residual fragments (CIRFs) were defined as asymptomatic non-obstructing residual fragments <4 mm on CT. 2,7,12…”
Section: Postoperative Evaluationmentioning
confidence: 99%
“…PCNL has a high stone-free rate (SFR), however, one of its major complications is hemorrhage, which is associated with the size of the percutaneous renal tract. [1][2][3][4] Efforts to decrease complications have focused on instrument size. Thus, less invasive and more refined instruments have been developed, such as those used during mini-PCNL and ultramini-PCNL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations